GROUNDED THEORY: FLEKSIBILITAS, TANTANGAN, DAN IMPLIKASI DALAM PENELITIAN EDUKASI - Mustafa, Desyana; Hermina, Dina (PT. Hasba Edukasi Mandiri, 2025)
This article examines Grounded Theory (GT), a qualitative methodological approach that aims to develop theory based on data obtained directly from the field. Introduced by Glaser and Strauss in 1967, GT emphasizes an inductive process that allows theory to develop naturally from data. The research process in GT involves simultaneous data collection and analysis through open, action, and selective coding stages that generate core categories. One of the distinctive features of GT is theoretical sampling, in which informants are selectively chosen to develop categories that emerge from the data. Although offering flexibility and contextualization, the use of GT faces challenges in terms of time, resources, and the need for analytical skills to manage bias. In a multidisciplinary context, particularly in the field of education, Grounded Theory has proven to be a powerful tool for exploring complex learning phenomena and interactions, as well as developing theory relevant to educational practice. The purpose of this article is to further explore the basic concepts, stages, and application of Grounded Theory, as well as to discuss the benefits and challenges associated with the process of developing field-based data theory. Artikel ini mengkaji Grounded Theory (GT), pendekatan metodologi kualitatif yang bertujuan mengembangkan teori berdasarkan data yang diperoleh langsung dari lapangan. Diperkenalkan oleh Glaser dan Strauss pada tahun 1967, GT menekankan pada proses induktif yang memungkinkan teori berkembang secara alami dari data. Proses penelitian dalam GT mencakup pengumpulan dan analisis data secara simultan dengan tahapan pengkodean terbuka, aksional, dan selektif yang menghasilkan kategori-kategori inti. Salah satu fitur khas GT adalah sampling teori, di mana informan dipilih secara selektif untuk mengembangkan kategori yang muncul dari data. Meskipun menawarkan fleksibilitas dan kontekstualisasi, penggunaan GT menghadapi tantangan dalam hal waktu, sumber daya, dan kebutuhan keterampilan analitis untuk mengelola bias. Dalam konteks multidisiplin, khususnya di bidang edukasi, Grounded Theory telah terbukti menjadi alat yang ampuh untuk menggali fenomena pembelajaran dan interaksi yang kompleks, serta mengembangkan teori yang relevan dengan praktik pendidikan. Tujuan dari artikel ini adalah untuk mengeksplorasi lebih jauh mengenai konsep dasar, tahapan, serta penerapan Grounded Theory, serta membahas manfaat dan tantangan yang terkait dalam proses pengembangan teori berbasis data lapangan.